'Good culture, bad culture': polygyny, cultural change and structural drivers of HIV in Papua New Guinea. Issue 9 (2nd September 2017) - Shih, Patti; Worth, Heather; Travaglia, Joanne; Kelly-Hanku, Angela
Abstract: Culture is often problematised as a key structural driver of HIV transmission in Papua New Guinea. Official HIV programmes, as well as church teachings, tend to focus on customary marital practices of polygyny and bride price payments as 'harmful traditions'. This focus can oversimplify the effects of current and historical nuances of cultural, political and economic change on sexual concurrency and gender inequality. Community-based healthcare workers in Southern Highlands Province explain that customary marital practices are now highly reconfigured from their traditional forms. A recent mining boom has financially advantaged local and travelling men, who are driving an increase of sexual concurrency, transactional sex and inflation of bride price payments. Healthcare workers suggest that the erosion of important social relationships and kinship obligations by the expanding cash economy has caused an intensification of individual male power while enhancing the vulnerability of women. Yet without the means to challenge the effects of uneven economic development, healthcare workers are left to target 'culture' as the central influence on individual behaviours. A commitment to address structural inequality by political leadership and in HIV prevention programmes and a careful contextualisation of cultural change is needed.